Equality, Self-determination, Administrative Discretion: Lessons from the Implementation of Jordan Principles in Two Provinces - Vandna Sinha; Josée G. Lavoie (McMaster University Library Press, 2024)
Canada has an obligation to implement Jordan's Principle in a way that achieves both substantive equality and self-determination. Both these principles require an approach that centres the full participation of First Nations, supports the development and provision of services tailored to culture and context, and enables differentiation across families and Nations. Canada's implementation of Jordan's Principle has relied so heavily on federal employees' use of administrative discretion that it has side-stepped the resource-intensive requirements of self-determination and substantive equality. Some use of administrative discretion is necessary to accommodate the diverse needs and context addressed by Jordan's Principle. However, excessive reliance on administrative discretion reproduces pre-existing, colonial power relations. Implementation of Jordan's Principle in keeping with the principles of self-determination and substantive equality requires: remedying the known gaps in existing policies and funding models that are being addressed through Jordan's Principle; providing First Nations with timely access to meaningful information about what can be funded through Jordan's Principle; ensuring that Jordan's Principle funding is extended on timelines and at levels that allow First Nations to take on responsibilities in tandem with their self-determined priorities; and ensuring First Nations' involvement in all levels of Jordan's Principle decision-making. Le Canada a l'obligation de mettre en œuvre le principe de Jordan de manière à réaliser à la fois l'égalité réelle et l'autodétermination. Ces deux principes requièrent une approche qui privilégie la pleine participation des Premières Nations, soutient le développement et la prestation de services adaptés à la culture et au contexte, et permet la différenciation entre les familles et les nations. La mise en œuvre du principe de Jordan par le Canada s'est tellement appuyée sur l'utilisation du pouvoir discrétionnaire des fonctionnaires fédéraux qu'elle a éludé les exigences d'autodétermination et d'égalité réelle, qui nécessitent beaucoup de ressources. Un certain recours au pouvoir discrétionnaire de l'administration est nécessaire pour répondre aux divers besoins et contextes visés par le principe de Jordan. Cependant, un recours excessif au pouvoir discrétionnaire administratif reproduit les relations de pouvoir coloniales préexistantes. La mise en œuvre du principe de Jordan dans le respect des principes d'autodétermination et d'égalité réelle exige de : combler les lacunes connues dans les politiques et les modèles de financement existants qui sont abordés dans le cadre du principe de Jordan ; fournir aux Premières Nations un accès opportun à des informations pertinentes sur ce qui peut être financé dans le cadre du principe de Jordan ; veiller à ce que le financement du principe de Jordan soit étendu dans des délais et à des niveaux qui permettent aux Premières Nations d'assumer des responsabilités en tandem avec leurs priorités autodéterminées ; et assurer la participation des Premières Nations à tous les niveaux de la prise de décision dans le cadre du principe de Jordan.